Èske Kay Nou Paré? - Hal S. Knowles, III; Kathleen C. Ruppert; Karla A. Lenfesty; Barbara Haldeman (EDIS)
Part of the Education + Action = Wind Damage Mitigation series by Kathleen C. Ruppert, Hal S. Knowles, Karla A. Lenfesty, and Barbara Haldeman that is now available in Spanish and Haitian Creole.